Vaccination contribute to the development of personal and herd immunity - N. V. Medunitsyn; Yu. V. Olefir; V. A. Merkulov; V. P. Bondarev (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The present article adduces the evidence in support of the need in the development of personalized vaccines and provides with case studies, substantiating the possibility of the mentioned approach. In order to personalize vaccines one should perform preliminary determination of antibody titers (or delayed-type hypersensitivity skin testing) and the subsequent correction of the immunity in patients with low titers of protective antibodies or hyperimmunization symptoms. Vaccine personalization does not require serious financial expenses. The article provides with the advantages of vaccine personalization and the measures that should be taken to achieve this goal. The difficulties of the personalization and the ways to overcome them are described in the article. Vaccine personalization does not require serious financial expenses. It will contribute to the development of preventive vaccination. Personalization of vaccines is necessary for achieving herd immunity, which leads to the reduction in the incidence of the mentioned infection and usually to the reduction of agent circulation. «Immune domain», which includes mostly recovered and vaccinated patients as well as naturally immuned individuals (by circulating infectious agents), plays a decisive role in the development of herd immunity. The effectiveness of herd immunity is reduced due to genetic variability of an agent, frequent vaccination refusals and rejections. Long-term herd immunity is stipulated by immunological memory.